RECOMBINANT YELLOW FEVER VIRUS WHICH EXPRESSES HETEROLOGOUS PROTEIN DURING REPLICATION - Keyer, V.V.; Shevtsov, A.B.; Kassymkhanova , A.S.; Baltabekova , A.Zh.; Shustov , A.V. (Eurasian Journal of Applied Biotechnology, 2018)
Yellow fever virus (YFV) is a model representative in the genus Flavivirus, which along with the YFV includes other human pathogens such as the tick-borne encephalitis virus, Zika virus, etc. The flaviviruses are prevalent worldwide and pose a risk to the population of Kazakhstan. Although the YFV itself is not present in Kazakhstan, a vaccine strain of the YFV may serve as a convenient model to study aspects of molecular virology of the flaviviruses. The vaccine strain 17D of the YFV was used to construct cDNA copy of a full-length viral genome. The cDNA was cloned in an E.coli plasmid. The 5’-end of the genome is placed under control of SP6 RNA polymerase promoter. This allows producing the virus’ genomic RNA using in vitro transcription. The 3’-end of the genome is engineered to be fused with antigenomic ribozyme (RBZ) of the hepatitis D virus. The RBZ cleaves itself off upon transcription to yield the correct 3’-end of the YFV genome. Also, a gene encoding green fluorescent protein (GFP) was inserted into the YFV genome in a position preceding structural proteins. An activity of foot-and-mouth disease autoprotease 2A was utilized to cleave off the GFP from viral polyprotein to ensure correct processing of the YFV proteins. Precautions were undertaken to preserve the 5’-cyclization signal which important for replication. The obtained molecular clone proved infectious. The virus (1612.YFV/GFP) was rescued from the plasmid by using in vitro transcription and RNA transfection. Thus an experimental system to produce recombinant flaviviruses was generated which may be advanced to produce live vaccines based on the YFV vector.